2020
DOI: 10.15698/cst2020.04.216
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus infections: Epidemiological, clinical and immunological features and hypotheses

Abstract: Coronaviruses (CoVs) are a large family of enveloped, positivestrand RNA viruses. Four human CoVs (HCoVs), the non-severe acute respiratory syndrome (SARS)-like HCoVs (namely HCoV 229E, NL63, OC43, and HKU1), are globally endemic and account for a substantial fraction of upper respiratory tract infections. Non-SARS-like CoV can occasionally produce severe diseases in frail subjects but do not cause any major (fatal) epidemics. In contrast, SARS like CoVs (namely SARS-CoV and Middle-East respiratory syndrome co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
304
0
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 341 publications
(323 citation statements)
references
References 67 publications
3
304
0
16
Order By: Relevance
“…In addition, coronaviruses that have rarely been tested systematically around the world may persist in the pharynx of asymptomatic people, representing a potential source of population immunity [29]. Furthermore, it should be noted that systematic studies of other coronaviruses (but not yet for SARS-CoV-2) have found that the percentage of asymptomatic carriers is equal to or even higher than the percentage of symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, coronaviruses that have rarely been tested systematically around the world may persist in the pharynx of asymptomatic people, representing a potential source of population immunity [29]. Furthermore, it should be noted that systematic studies of other coronaviruses (but not yet for SARS-CoV-2) have found that the percentage of asymptomatic carriers is equal to or even higher than the percentage of symptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…During the previous SARS outbreak, a common transmission pattern hypothesis was that SARS-CoV virus silently infected asymptomatic patients, which may have led to population immunity against infection (herd immunity) that may explain the eradication of the virus, although this is yet to be confirmed [72]. Although a study suggests that coronavirus antibodies are highly prevalent in the general population after exposure to four non-SARS coronavirus strains [73], there is no definitive evidence on whether permanent immunity would be generated against other CoV species, such as SARS-COV-2.…”
Section: Salivary Immunity Monitoring For Covid-19mentioning
confidence: 99%
“…8 One month later, 83,652 cases were confirmed, with 2,791 deaths (3.4% mortality). 9 Cases were reported in 24 countries on 5 continents. 10 In Brazil, specifically, by March 3, 488 suspected cases had been registered, in 23 states.…”
Section: Adults and The Elderlymentioning
confidence: 99%